1967
DOI: 10.3758/bf03212461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of discriminability and irrelevant information on absolute judgments’

Abstract: The effects of irrelevant information (0, I, 2,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1971
1971
1990
1990

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The results of a large number of studies argue for a progressively relaxed cutoff in any discrimination model that postulates a stopping criterion based on S's expected accuracy. These experiments measured time and accuracy when the discrimination difficulty varied randomly from trial to trial (Henmon, 1906;Lemmon, 1927;Kellogg, 1931;Johnson, 1939;Festinger, 1943a, b;Birren & Botwinick, 1955;Botwinick, Brinley, & Robbin, 1948;Thurmond & Alluisi, 1963;Morgan & Alluisi, 1967;Pickett, 1964Pickett, , 1967. For trials on which the more difficult stimuli occurred: (1) mean RTs were slower and (2) error rates were higher.…”
Section: Models For Discriminationmentioning
confidence: 99%
“…The results of a large number of studies argue for a progressively relaxed cutoff in any discrimination model that postulates a stopping criterion based on S's expected accuracy. These experiments measured time and accuracy when the discrimination difficulty varied randomly from trial to trial (Henmon, 1906;Lemmon, 1927;Kellogg, 1931;Johnson, 1939;Festinger, 1943a, b;Birren & Botwinick, 1955;Botwinick, Brinley, & Robbin, 1948;Thurmond & Alluisi, 1963;Morgan & Alluisi, 1967;Pickett, 1964Pickett, , 1967. For trials on which the more difficult stimuli occurred: (1) mean RTs were slower and (2) error rates were higher.…”
Section: Models For Discriminationmentioning
confidence: 99%
“…In particular, Gregg (1954), Hodge (1959), Montague (1965), Egeth (1966), and Morgan and Alluisi (1967) reported substantial interference effects due to variation along dimensions of the stimulus display that were supposedly irrelevant, while Archer (1954), Morin et al (1961), Fitts and Biederman (1965), and Imai and Garner (1965) reported no such interference. This literature has been reviewed in some detail by Egeth (1967).…”
mentioning
confidence: 99%
“…This explanation is made more plausible by evidence in the literature that Ss cannot "filter out" color when it is an irrelevant dimension (Egeth & Pachella, 1969;Morgan & Alluisi, 1967).…”
Section: Methodsmentioning
confidence: 99%